Annotated checklist and keys to the Orthotrichaceae of Malawi, together with new country records for East Africa. (June 2015) - Wilbraham, Joanna
<x content-type="archive" xml:space="preserve">Abstract</x> This paper provides an updated checklist of the Orthotrichaceae occurring in Malawi. Six species (Groutiella tomentosa (Hornsch.) Wijk & Margad., Macromitrium soulae Renauld & Cardot, Schlotheimia badiella Besch., Zygodon erosus Mitt., Zygodon intermedius Bruch & Schimp. and Zygodon reinwardtii (Hornsch.) A.Braun in B.S.G.) are reported as new to Malawi. A key to these species is provided. Illustrations are included for the two poorly known species Macromitrium soulae and Schlotheimia badiella. In addition, Schlotheimia badiella is recorded new to Tanzania, Macromitrium sulcatum (Hook.) Brid. is recorded new to Burundi and Macromitrium serpens (Bruch ex Hook. & Grev.) Brid. is removed from the Malawi checklist but reported as new to Kenya.